Specific erythrocyte binding capacity and biological activity of plasmodium falciparum-derived rhoptry-associated protein 1 peptides (2004)
Rhoptry-associated protein 1 (RAP1) is a merozoite antigen within Plasmodium falciparum rhoptries as yet having no specific function described for it. Synthetic peptides spanning the RAP1 sequence were tested in erythrocyte binding assays to identify possible RAP1 functional regions. Five high activity binding peptides (HABPs) were identified; 26201, 26202, 26203 and 26204 spanned residues –K540 within RAP1 Cys region, whilst 26188 (–Y220) was located in p67 amino terminal. The results showed that peptide binding was saturable, some HABPs inhibited in vitro merozoite invasion and specifically bound to a 72 kDa protein in red blood cell membrane. HABP possible function in merozoite invasion of erythrocytes is also discussed.